Sexual Partnership-Level Correlates of Intimate Partner Violence Among Men Who Have Sex with Men and Transgender Women in Lima, Peru - Passaro, R. Colby (2020)
To improve understanding of factors associated with intimate partner violence (IPV) and explore its role in sexually transmitted infection (STI) acquisition, we analyzed partnership-level correlates of IPV among men who have sex with men (MSM) and transgender women (TW) in Peru. In a 2017 cross-sectional study of rectal STI screening and HIV prevention, MSM/TW completed a sociobehavioral survey addressing demographic characteristics, sexual risk behaviors, and substance use, and were tested for rectal gonorrhea and chlamydia, syphilis, and HIV. Generalized estimating equations estimated individual- and partner-level correlates of IPV. Of 576 participants (median age, 27 years), 7.9% (36/456) of MSM and 15.0% (18/120) of TW reported IPV with ≥ 1 of their last three partners. MSM/TW reporting IPV were more likely to meet criteria for an alcohol use disorder (74.1%) than participants reporting no IPV (56.7%; p <.01). Physical violence (4.5% MSM; 9.2% TW) was associated with stable partnerships (aPR 3.79, 95% CI 1.79–8.04), partner concurrency (4.42, 1.19–16.40), and participant alcohol (4.71, 1.82–12.17) or drug use (5.38, 2.22–13.02) prior to sex. Psychological violence (4.5% MSM; 5.0% TW) was associated with stable partnerships (2.84, 1.01–7.99). Sexual IPV was reported by 1.1% of MSM and 5.0% of TW. Physical, psychological, and sexual IPV were reported in sexual partnerships of Peruvian MSM and TW, particularly with stable partners and in conjunction with substance use.